Survey on the Effects of 4-week of the Special Aerobic Training on Hydrogen sulfide Levels in Hippocampus of Wistar Male Rats - farhad azimi; Marefat Siahkouhian; Farnaz Seifi; Roghayeh Afroundeh (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: Hydrogen sulfide an important role in the body's physiological functions. The aim of the present study was to survey on the effects of 4-week of the special aerobic training on CBS, SAM and H2S levels in hippocampus of Wistar male rats. Methods: Fourteen male Wistar rats (12 weeks old and weight 195 ± 20 g) were randomly divided into two groups including: control and aerobic training. Training group trained 5 days a week for 4 weeks (15 minutes at 10 m/min). ). CBS and SAM mRNA expression in hippocampus was measured by Real time-PCR techniqiue and the ELISA method was used to measure H2S. For data analysis, MANOVA and Eta and Omega squared tests were used to determine the effect size at 95% confidence level (p